A randomized controlled trial on the use of budesonide/formoterol (symbicort) as an alternative reliever medication for mild to moderate asthmatic attack in adult patients in Emergency Department, HUSM - Chew Keng, Sheng (Pusat Pengajian Sains Perubatan, 2012)
This study is done to evaluate the effectiveness of symbicort (a combination of formoterol and budesonide) as an alternative reliever in mild to moderate acute axacerbation of bronchial asthma Patients who fulfilled the criteria of mild or moderate asthmatic attack and agreed to participate in this study were randomly assigned to either nebulized salbutamol or symbicort turbuhaler as the treatment. Objective and clinical parameters such as respiratory mte (RR), oxygen saturation (SP02), peak expiratory flow mte (PEFR) and fraction of exhale nitric oxide (FENO) were recorded before and after treatment. Subjective assessment using visual analog score and 5-point Likert scale were also taken. The patients were reassessed 15 minutes later for need of further treatment After randomization, 17 out of 32 patients were chosen to receive nebulized salbutamol and another 15 patients to receive symbicort. There were significant improvements in respiratory mte (RR), oxygen satumtion (SP02) and PEFR in patients received symbicort turbuhler (p=O.OOI, p=0.027 and p=<O.OOJ respectively). This result is significant in patients receiving nebulized salbutamol as well. When compared between these two groups, no significant difference was demonstmted. In terms of subjective parameters using 'Visual Analog Score' and '5-point Likert Scale' of breathlessness, it also showed that there were no significant difference in patients who received symbicort turbuhaler or nebulized salbutamol. Symbicort has the potential to be used as an alternative treatment for patients with mild to moderate exacerbation of asthma as there were no significant difference in terms of objective and subjective improvements at least for the first 15 minutes.